Literasi Digital Merangkul Teknologi Membekali Siswa di Era Digital pada SMA N 12 Tanjung Jabung Barat - Fitra Kebesa Miten; Arif Setiadi; Sugeng Wibowo; Fadhli Azis; Telly Zuvilla Irwanto; Arie Agus Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of information and communication technology in Indonesia continues to grow rapidly, as evidenced by the internet penetration rate reaching 73.3% in 2019 (APJII). With 144.19 million out of 196.71 million Indonesians having internet access, the country has become the largest digital economy market in Southeast Asia (Google e-Conomy SEA, 2020). West Java Province recorded the highest number of internet users, followed by Central Java, DKI Jakarta, and Jambi. In response to this development, President Joko Widodo has designated accelerating digital transformation towards becoming a